Principles of Islam and Social Integration: A Conceptual Framework for Promoting Peaceful Coexistence in South Korea - Abdul Salam Noh Se Ik; Syaikhoni Jazuli; Rohmah, Siti; Nur Chanifah (Pustaka Peradaban, 2024)
The growth of Islam as a minority group in South Korea necessitates various efforts to ensure that the Muslim community is accepted as part of the broader societal framework. The recent indications of Islamophobia in Korea further emphasize the need to shape a positive image of Islam within Korean society. Fear and expressions of hatred towards Islam and Muslims can emerge as a result of misunderstanding, stereotypes, or misinformation. This article proposes the application of representative Islamic principles to foster positive relationships with the surrounding community. These principles include the principles of peace, multiculturalism, and the concept of rahmatan lil alamin (universal mercy). The implementation of these principles can serve as a foundation for Muslims to be accepted and coexist harmoniously with other groups. This is expected to provide a deeper understanding of the values of Islam as a conceptual framework for promoting harmony in a society characterized by cultural and religious diversity. Pertumbuhan Islam sebagai kelompok minoritas di Korea Selatan menuntut perlunya berbagai upaya agar umat Islam diterima sebagai bagian dari kerangka sosial yang lebih luas. Adanya indikasi Islamopobia di Korea belakangan ini semakin menegaskan perlunya membentuk citra positif tentang Islam dalam masyarakat Korea. Ketakutan dan ekspresi kebencian terhadap Islam dan umat Muslim, dapat muncul sebagai hasil dari ketidakpahaman, stereotip, atau informasi yang salah. Artikel ini mengusulkan penerapan prinsip-prinsip Islam yang representatif untuk membentuk hubungan positif dengan masyarakat sekitar. Prinsip-prinsip ini mencakup prinsip perdamaian, multikulturalisme, dan konsep rahmatan lil alamin (rahmat universal). Implementasi prinsip-prinsip ini dapat menjadi dasar bagi umat Islam untuk diterima dan hidup berdampingan secara harmonis dengan kelompok lain. Hal ini diharapkan dapat memberikan pemahaman yang lebih mendalam tentang nilai-nilai Islam sebagai kerangka konseptual dalam mempromosikan harmoni dalam masyarakat yang ditandai oleh keberagaman budaya dan agama.